Impact of Covid-19 Pandemic on Tourism Research: A Bibliometric Analysis Using Cite Spa - baser, gozdegul; Ehtiyar, Rüya (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This research aims to review the extant literature on Covid-19 using bibliometric analysis in an attempt to gauge the evolving state of tourism research since the beginning of the Covid-19 pandemic.The Thompson Reuters’ Web of Science Core Collection database was chosen to collect the bibliographic data of 3179 publications for the period of 2020- February 2022. CiteSpace software was then employed to analyze and visualize the documents. Co-citation analysis and co-occurrence of keywords were carried out in terms of bibliometric analysis. The findings revealed a significant increase in the diversity of topics and subtopics addressed by researchers regarding Covid-19. This bibliometric review provides a comprehensive and objective review of Covid-19 related publications in the tourism field. It extends previous reviews by visualizing the underlying structure via CiteSpace software and adding current publications. Furthermore, this study may help researchers better evaluate and monitor research trends in tourism during the Covid-19 pandemic.